Use of Implantable Venous Port Systems in the Treatment of Children with Orphan Diseases (Mucopolysaccharidosis and Pompe Disease): Case Series - M. Yu. Rykov (Voprosy Sovremennoj Pediatrii, 2015)
Many orphan diseases in children require life-long and regular intravenous enzyme replacement therapy. The article describes the first Russian practice of implanting venous port systems in 12 patients with type I and II mucopolysaccharidosis and Pompe disease (6 months to 17 years old) to create long-term venous access. Currently, implantable venous port systems are used in 9 (75%) of 12 patients. 4 cases of thrombosis are observed in 3 patients. All of them have been successfully treated. 1 patient had a rotation of the port camera with a membrane facing downwards due to violation of an implantation technique. The camera was adjusted during the second operation.